2021
DOI: 10.2139/ssrn.3783768
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Insolvency Gap: First-Round Effects of Policy Responses on SMEs

Abstract: COVID-19 placed a special role to fiscal policy in rescuing companies short of liquidity from insolvency. In the first months of the crisis, SMEs as the backbone of Europe's real economy benefited from large and mainly indiscriminate aid measures. Avoiding business failures in a whatever it takes fashion contrasts, however, with the cleansing mechanism of economic crises: a mechanism which forces unviable firms out of the market, thereby reallocating resources efficiently. By focusing on firms' pre-crisis fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Of course, the findings that emphasize the idea of zombification of SMEs in the pre-and post-crisis periods (Dörr et al,2021) as well as the contrary findings that forecast that business failures will arise from a reduction in loans to the corporate sector (Gourinchas et al, 2021). can be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the findings that emphasize the idea of zombification of SMEs in the pre-and post-crisis periods (Dörr et al,2021) as well as the contrary findings that forecast that business failures will arise from a reduction in loans to the corporate sector (Gourinchas et al, 2021). can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary wage subsidies and restructuring of debts of SMEs that are unsustainable due to their debts and review of bankruptcy procedures are advocated, especially to support firms affected by negative demand and productivity shocks (Blanchard et al, 2020). For example, it has been shown that in Germany, the fiscal policy response to COVID-19 triggered backlog bankruptcies, which was particularly evident among financially weak small firms (Dörr et al, 2021). On the other hand, some studies suggest that business failures will result from the decrease in loans to the corporate sector (Gourinchas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The following eight main measures are distinguished: debt finance, employment support, tax, business costs, other finance, demand, business climate, and business advice (Adian et al, 2020). In Germany, fiscal policy measures, including liquidity subsidies and government guarantees, temporary change in insolvency law, short-time work (STW) scheme, played a major role in responding to the COVID-19 crisis (Dörr et al, 2021 Today, even under the conditions of the COVID-19 pandemic, favorable conditions are created in Georgia to start a business. According to the 2020 Index of Economic Freedom, Georgia ranks 12 th out of 180 countries in the world and 6 th in the European region (Miller et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%